N, N‐Diformylmescaline: A novel analogue of mescaline detected in Queensland. Issue 2 (28th November 2022) - Gallagher, Ryan; McLaughlin, Maddison G.; Blakey, Karen; Wermuth, Urs D.; Boyd, Sue; McGowan, Jenny
Abstract: N, N ‐Diformylmescaline, a novel analogue of mescaline, has recently been detected in Australia in two unrelated seizures. To confirm the identification, a three‐step synthesis from 3, 4, 5‐trimethoxyphenylacetic acid was devised. However, purification of the final product proved problematic with the compound prone to degradation in solution. Analysis of the compound by LC–MS indicated that the compound was unstable under acidic and basic conditions, breaking down to N ‐formylmescaline. Further degradation to mescaline was observed when the compound was dissolved in hydrochloric acid for an extended period of time suggesting that N, N ‐diformylmescaline may be a prodrug for mescaline. The GC–MS, NMR and FTIR data for the seized compound are presented along with details of the synthesis and studies of the compound's stability in solution. Abstract : N, N‐Diformylmescaline, a novel analogue of mescaline, has recently been detected in Australia in two unrelated seizures. To confirm the identification, a three‐step synthesis from 3, 4, 5‐trimethoxyphenylacetic acid was devised. The GCMS, NMR and FTIR data for the seized compound are presented along with details of the synthesis and studies of the compounds stability in solution.